Study of distribution of biologically active substances from flowers of helichrysum arenarium between phases of the extraction system - N. N. Boyko; E. T. Zhilyakova; A. Yu. Malyutina; D. K. Naplekov; N. N. Shestopalova; D. S. Martceva; O. O. Novikov; D. I. Pisarev; P. G. Mizina (Фармация и фармакология (Пятигорск), 2019)
The aim of this study is to confirm the adequacy of the proposed hypothesis, which explains and quantitatively describes the distribution of biologically active substances (BAS) within the extraction system consisting of Helichrysum arenarium flowers and the solvent using a regressive analysis for the theoretically predicted coordinates.Materials and methods. For this research, milled officinal flowers of Helichrysum arenarium (Helichrysum arenarium L. flores) were used. The analysis of the extractions was carried out by RP HPLC method. Isosalipurposide, salipurposide, and chlorogenic acid of >98.0% purity were used as reference substances. The analytical wavelengths were 370, 290, and 325 nm. Results. The obtained experimental data are well-approximated by regressive linear equations in the theoretically predicted coordinates 1/C=f(V) and ln(b/a)=f(1/T). Wherein, the coefficient of determination of regressive equations was R2>0.998, which indicates functional dependence between the studied parameters and confirms the adequacy of the developed mathematical model. The experimental work identified the necessity of implementation of additional constant values into the mathematical model.Conclusion. A new hypothesis was proposed to explain and quantitatively describe the distribution of BAS in the extraction system of Helichrysum arenarium flowers and 80% ethanol. With this working hypothesis, mathematical models were developed and their adequacy was proved using a regressive analysis in the theoretically predicted coordinates. The results obtained could not deny that a mechanism of BAS distribution between the phases is explained and described by the classic Boltzmann distribution for discrete values of molecular energy (or quantum distribution according to Fermi and Dirac).